Genome Factor. - Conley, Dalton (Princeton University Press, 2017)
"For a century, social scientists have avoided genetics like the plague. But in the past decade, a small but intrepid group of economists, political scientists, and sociologists have harnessed the genomics revolution to paint a more complete picture of human social life than ever before. The Genome Factor describes the latest astonishing discoveries being made at the scientific frontier where genomics and the social sciences intersect. The Genome Factor reveals that there are real genetic differences by racial ancestry--but ones that don't conform to what we call black, white, or Latino. Genes explain a significant share of who gets ahead in society and who does not, but instead of giving rise to a genotocracy, genes often act as engines of mobility that counter social disadvantage. An increasing number of us are marrying partners with similar education levels as ourselves, but genetically speaking, humans are mixing it up more than ever before with respect to mating and reproduction. These are just a few of the many findings presented in this illuminating and entertaining book, which also tackles controversial topics such as genetically personalized education and the future of reproduction in a world where more and more of us are taking advantage of cheap genotyping services like 23andMe to find out what our genes may hold in store for ourselves and our children. The Genome Factor shows how genomics is transforming the social sciences--and how social scientists are integrating both nature and nurture into a unified, comprehensive understanding of human behavior at both the individual and society-wide levels."--